The aging kidney is characterized by tubuloinflammaging, a phenotype associated with MHC-II gene expression - Sinning, Julius; Funk, Nils David; Soerensen-Zender, Inga; Wulfmeyer, Vera Christine; Liao, Chieh Ming; Haller, Hermann; Hinze, Christian; Schmidt-Ott, Kai Martin; Melk, Anette; Schmitt, Roland (Frontiers in Immunology, 2023)
Even during physiologic aging, the kidney experiences a loss of mass and a progressive functional decline. This is clinically relevant as it leads to an increased risk of acute and chronic kidney disease. The kidney tubular system plays an important role in the underlying aging process, but the involved cellular mechanisms remain largely elusive. Here we show that during normal kidney aging, tubular cells adopt an inflammatory phenotype, characterized by the expression of MHC class II related genes. In our analysis of bulk and single cell transcriptional data we found that subsets of tubular cells show an age-related expression of Cd74, H2-Eb1 and H2-Ab1 in mice and CD74, HLA-DQB1 and HLA-DRB1 in humans. Expression of MHC class II related genes was associated with a phenotype of tubular cell senescence, and the selective elimination of senescent cells reversed the phenotype. Exposure to the Cd74 ligand MIF promoted a pro-senescent phenotype in tubular cell cultures. Together, these data suggest that during normal renal aging tubular cells activate a program of 'tubuloinflammaging', which might contribute to age-related phenotypical changes and to increased disease susceptibility.